Pilot study on using a photometric capsule to stratify patients with suspected nonvariceal upper gastrointestinal bleeding into emergency versus elective endoscopy - Brand, Markus; Vogt, Gina; Hann, Alexander; Weich, Alexander; Kudlich, Theodor; Lux, Thomas; Weber, Marie; Wedi, Edris; Kuellmer, Armin; Schmidt, Arthur; Brunk, Thomas; Meining, Alexander (Endoscopy, 2025)
Current guidelines recommend early endoscopy (within 24 hours) for hemodynamically stable patients with suspected nonvariceal upper gastrointestinal hemorrhage (NVUGIH). We evaluated the use of a new photometric capsule examination (PCE) for stratification of patients into emergency (within 12 hours) and elective (within 48–96 hours) endoscopy.Patients with suspected NVUGIH were enrolled at four centers and received PCE. Patients with a positive capsule result (Group A) underwent emergency esophagogastroduodenoscopy (EGD) within 12 hours after admission. Patients with a negative result (Group B) received a proton pump inhibitor twice daily and underwent EGD within 48–96 hours. If signs of acute bleeding occurred in the meantime, an emergency endoscopy was performed. The primary end point was the rate of avoided early endoscopies in Group B.73 patients were included (median Glasgow–Blatchford score 11 [interquartile range 5]). In Group A (n = 32), nine patients (28.1%) were found to have active bleeding. Emergency endoscopy was avoided in 95.1%, as two patients in Group B (n = 41) received an emergency endoscopy, both without active bleeding. Two patients did not receive endoscopy and were therefore excluded from analysis. Active bleeding was excluded by PCE in the remaining 37 patients (sensitivity and negative predictive value 100%). No technical, PCE-related, or bleeding-related complications occurred during the follow-up period (30 days).PCE was a quick and easy-to-use method with a high negative predictive value for suspected NVUGIH and could be used to identify patients in whom emergency endoscopy can be avoided.